Logistic regression for the classification and risks for professional perfomance - Cortez Gutiérrez, Hernán Óscar; Cortez Gutiérrez, Milton Milcíades; Grados Gamarra, Juan Herber; Rubiños Jiménez, Santiago Linder; Espinoza Flores, Braulio Pedro (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The objectives were to determine the factors associated with professional perfor- mance. To establish a relationship between the dependent variable professional performance and direct support of job quality, logistic regression was used. In conclusion, logistic regression establishes an association between professional performance and direct support: The Wald statistic is 2.79 and a significance of 0.094<0.10. The association simulation between professional performance and direct support has Chi-square Yates of 0.313 and a significance of 0.576>0.10. The Pearson statistic is 0.78 and a significance of 0.001. The predictive confidence interval for correlation has been determined as: [0.41,1].